2019
DOI: 10.1080/10903127.2019.1575498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physician-Staffed Emergency Medical Services (P-EMS) on the Outcome of Patients with Severe Traumatic Brain Injury: A Review of the Literature

Abstract: Introduction: Traumatic injury is the fourth leading cause of death in western countries and the leading cause of death in younger age. However, it is still unclear which groups of patients benefit most from advanced prehospital trauma care. A minimal amount is known about the effect of prehospital physician-based care on patients with specifically traumatic brain injury (TBI). The aim of this review is to assess the effect of physician-staffed Emergency Medical Services (EMS) on the outcome of patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Our analysis controlled for all of these factors, as well as for other potential confounders such as gender, type and mechanism of injury, and HEMS assistance. Nonetheless, residual confounding due to unobserved variables – such as hemodynamic, respiratory and physiologic parameters that are known to affect mortality in trauma patients [ 5 , 10 , 11 , 25 ]—cannot be excluded. Furthermore, excluding patients with missing or incomplete prehospital time and reporting solely on in-hospital mortality, not taking into account prehospital mortality, might have caused a certain degree of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis controlled for all of these factors, as well as for other potential confounders such as gender, type and mechanism of injury, and HEMS assistance. Nonetheless, residual confounding due to unobserved variables – such as hemodynamic, respiratory and physiologic parameters that are known to affect mortality in trauma patients [ 5 , 10 , 11 , 25 ]—cannot be excluded. Furthermore, excluding patients with missing or incomplete prehospital time and reporting solely on in-hospital mortality, not taking into account prehospital mortality, might have caused a certain degree of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most Japanese tertiary medical centers, including the study site, run a hospital-based emergency physician (EP) delivery system for early initiation of advanced trauma care [12]. Nevertheless, the effect of EP deployment to the prehospital scene on outcomes among injured patients remains controversial: Several studies have shown that EP involvement in prehospital trauma care is associated with improved survival in patients with trauma [13][14][15][16][17][18][19] whereas other studies report no significant differences [20][21][22][23] or decreased survival [24]. Although injured patients requiring definitive intervention, such as surgery or TAE, are an extremely time-sensitive population, previous studies have not focused on this important trauma subset [13][14][15][16][17][18][19][20][21][22][23][24], and little is known regarding whether and how an EP delivery system affects the preoperative time course and patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the effect of EP deployment to the prehospital scene on outcomes among injured patients remains controversial: Several studies have shown that EP involvement in prehospital trauma care is associated with improved survival in patients with trauma [13][14][15][16][17][18][19] whereas other studies report no significant differences [20][21][22][23] or decreased survival [24]. Although injured patients requiring definitive intervention, such as surgery or TAE, are an extremely time-sensitive population, previous studies have not focused on this important trauma subset [13][14][15][16][17][18][19][20][21][22][23][24], and little is known regarding whether and how an EP delivery system affects the preoperative time course and patient survival. Additionally, despite hospital LOS being a sensitive indicator that reflects patients' disease burden, previous studies have not clarified how EP involvement in prehospital trauma care affects this important parameter, as compared with ELSTs [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-hospital physicians have the potential to restore adequate flow and physiology in severely sick or injured patients, but the subject remains debated [1][2][3][4][5][6]. P-EMS are resource demanding compared with standard paramedic-staffed services [7], and more research is needed to evaluate any potential effects of p-EMS [1,8,9]. High-quality research relies on data quality and uniform documentation is essential to ensure reliable and valid data.…”
Section: Introductionmentioning
confidence: 99%